THE EFFECT OF SERVICE QUALITY, PRODUCT, PRICE AND HALAL LABEL ON CUSTOMER SATISFACTION; A STUDY AT THE COFFEE SHOP MELIPIR KARAWACI, TANGERANG BANTEN - Suardi, Didi; Simatupang, Aisyah Defy Rahmayani; Jamaludin, Nur; Wulandari, Fithri; Nur’Aeni, Putri (Manager : Jurnal Ilmu Manajemen, 2024)
This study aims to determine the effect of service quality, product, price and halal label on consumer satisfaction at Kedai Melipir Kopi Karawaci. The method used in this study is a quantitative method with the research instrument in the form of a questionnaire. The analytical technique used in this research is descriptive quantitative by using the Partial Least Square (PLS) analysis technique. Respondents in this study amounted to 100 respondents who were determined using purposive sampling technique. The results show that the service quality variable (X1) has no effect on consumer satisfaction (Y) as evidenced by the calculation of p-values ​​worth 0.878, the product variable (X2) affects the consumer satisfaction variable (Y) as evidenced by the calculation of p-values ​​worth 0.020, the variable price (X3) has an effect on the consumer satisfaction variable (Y) as evidenced by the calculation of p-values ​​worth 0.023, and the halal label variable (X4) has no effect on consumer satisfaction (Y) as evidenced by showing the results of the calculation of p-values ​​worth 0.471 so that the hypothesis test H0 accepted, H4 is rejected, this indicates that the halal label has no effect on consumer satisfaction.